EFEKTIVITAS EKSTRAK ETANOL MADU RANDU DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Klebsiella pneumoniae - Aliyah Sundari; Aisyah Syifana Aulia (LPPM Universitas Abdurrab, 2025)
Klebsiella pneumoniae is a pathogenicbacteria that causes infectious diseases in humans. Klebsiella pneumoniae is an opportunistic bacterium that always shows higher resistance to antibiotics. The development of herbal medicines as an alternative to antibiotics is an effort to overcome bacterial resistance to antibiotics. There are substances in randu honey that have bactericidal and bacteriostatic properties, such as antibiotics. Therefore, the aim of the research is to find out how effective the ethanol extract of randu honey is in stopping the development of Klebsiella pneumoniae bacteria. This research used diffusion techniques to test various concentrations of randu honey extract. The data collected shows the diameter of the zone that inhibits the use of honey extract to prevent the growth of the test bacteria. To analyze the data, a one-way ANOVA test was used using the SPSS 29.0 program. The results showed that inhibition started with a 60% concentration, showing an inhibitory zone diameter of 14.25 ± 2.06 mm, an 80% concentration with an inhibitory zone diameter of 16.25 ± 1.89 mm, and a 100% concentration with an inhibitory zone diameter of 18.25 ± 1.71 mm. The greater the concentration level of the extract, the greater the diameter of the inhibition zone formed. It can be concluded that the minimal concentration of extract that can be used to inhibit bacterial growth is 60%.